IMPLEMENTASI MANAJEMEN STRATEGI KEPEMIMPINAN BU NYAI DALAM PEMBENTUKAN KARAKTER SANTRI (STUDI KASUS PESANTREN BANYUMAS) - Nisa, Wifdatun; Burhanudin Yusuf, Enjang (Universitas Nahdlatul Ulama Al Ghazali Cilacap, 2025)
This study aims to describe the implementation of Bu Nyai's leadership strategy management in instilling the characteristics of students in several Islamic boarding schools in Banyumas Regency. The main focus of this study is to explore the central role of Bu Nyai as a spiritual leader, educator, and manager of Islamic boarding schools, as well as the strategies used in shaping the character of students through an exemplary approach, habituation, and internalization of Islamic values. This study uses a qualitative approach with a case study method. Data collection techniques are carried out through in-depth interviews, participatory observation, and documentation. The results of the study indicate that Bu Nyai has a significant role in shaping the character of students, especially through a value-based leadership strategy, intensive personal communication, and the integration of moral values ​​in the daily activities of students. The main values ​​instilled include honesty, responsibility, independence, and discipline. The conclusion of this study confirms that the success of instilling the character of students is largely determined by the strength of Bu Nyai's leadership which prioritizes a spiritual, humanist, and participatory approach.